A dataset for article, "Demonstration of a kW-scale solid oxide fuel cell-calciner for power generation and production of calcined materials" - Nabavi, Seyed Ali; Erans moreno, María; Manovic, Vasilije (Cranfield University, 2019)
A dataset for article, "Demonstration of a kW-scale solid oxide fuel cell-calciner for power generation and production of calcined materials"
Keywords: 'solid oxide fuel cells'; 'calcination'; 'power generation applications'; 'Direct Air Capture'; 'Energy Generation; Conversion and Storage Engineering'; 'Carbon Capture Engineering (excl. Sequestration)'